Female breast cancer statistics of 2010 in China: estimates based on data from 145 population-based cancer registries - Zeng, Hongmei; Zheng, Rongshou; Zhang, Siwei; Zou, Xiaonong; Chen, Wanqing (Journal of Thoracic Disease; Vol 6, No 5 (May 08, 2014): Journal of Thoracic Disease, 2014)
Background: The aim of the study is to provide incidence and mortality data of female breast cancer at national level of China in 2010. Methods: A total of 145 population-based cancer registries submitted qualified cancer incidence and mortality data to National Cancer Registration Center of China. Based on the qualified cancer registries' data, we estimated the overall breast cancer incidence and mortality data of China in 2010 and reported breast cancer statistics by age and geographical area. Results: The estimated number of female breast cancer cases was about 208 thousand. The crude incidence rate, age-standardized rate by China and World population were 32.43 per 100,000, 25.89 per 100,000 and 24.20 per 100,000, respectively. The incidence rates were higher in urban area than in rural area. And the incidence rates in Eastern area and Middle area were similar and higher that those in Western areas. The estimated number of female breast cancer death in 2010 of China was about 55.5 thousand. The crude, age-standardized mortalities by China population and World population were 8.65 per 100,000, 6.56 per 100,000 and 6.36 per 100,000, respectively. The mortality rates by geographical area had similar pattern to the incidence rates. Conclusions: Breast cancer is still a major health burden for Chinese women especially in urban area. Prevention strategies such as weight control, high-quality screening and diagnosis may help control the disease.